Pemberdayaan Kelompok PKK Desa Ilomata melalui Wirausaha Keripik Pisang Aneka Rasa - Tri Handayani; Nurhayati Olii; Kartika Chandra Pelangi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Ilomata Village is one of the villages in Gorontalo District which has the potential of banana farming commodities, but it has not been utilized optimally. The aim of this community service activity are empowering the Ilomata Village PKK group through training activities for making various flavors of banana chips, simple bookkeeping training and product marketing training. The method applied is training and mentoring, whose activities include 1) Training in making various flavored banana chips; 2) Simple bookkeeping training; 3) Product marketing training; and 4) Mentoring in determining the name of the product, making packaging labels, and handling PIRT distribution permit. The results of the activity showed that the PKK group members understood and had skills in making banana chips with various flavors, doing simple bookkeeping and marketing the product. The availability of a banana chip product named banana chips I-Bas (Ilomata-Banana chips) with No. distribution license for PIRT 214750201001324 and has been marketed both offline and online. Thus, the empowerment of the PKK groups through banana chips entrepreneurship can increase the utilization of the potential of the banana commodity in line with the increased understanding and skill of PKK group members in making and marketing various flavored banana chips products.